2023
DOI: 10.1007/s11240-023-02457-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-strategy approach towards optimization of maturation and germination in radiata pine somatic embryogenesis

Abstract: Somatic embryogenesis is a powerful technique for forestry improvement programs when implementing multi-varietal forestry. However, it still faces some bottlenecks to be e cient in many forestry species. In this work we have studied the effect of some physico-chemical modi cations at proliferation, maturation and germination stages of Pinus radiata D. Don somatic embryogenesis, as well as the impact of this modi cations on plant conversion, survival, and on the morphology and biochemical pro le (carbohydrate a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…This may be due to the fact that in both cases, the data were given in fresh weight and ECLs are mostly water (around 10% dry weight, Peng et al 2020) whereas ses have dry weight values around 30% (data not shown). If compared with other studies carried out in our laboratory with radiata pine somatic plantlets after six weeks of germination, the amino acid pro les vary considerably (Castander-Olarieta et al 2023). In that work it was shown that arginine is one of the most abundant free amino acids, contrasting with the results obtained at embryo level.…”
Section: Discussionmentioning
confidence: 81%
“…This may be due to the fact that in both cases, the data were given in fresh weight and ECLs are mostly water (around 10% dry weight, Peng et al 2020) whereas ses have dry weight values around 30% (data not shown). If compared with other studies carried out in our laboratory with radiata pine somatic plantlets after six weeks of germination, the amino acid pro les vary considerably (Castander-Olarieta et al 2023). In that work it was shown that arginine is one of the most abundant free amino acids, contrasting with the results obtained at embryo level.…”
Section: Discussionmentioning
confidence: 81%
“…Although in a number of conifer species, progress has been made regarding somatic embryogenesis research, only a handful of somatic embryogenesis systems, those being Picea abies [ 20 , 21 ], Pinus banksiana [ 7 ] and Pinus radiata [ 22 ], can be applied for practical production. The stability of somatic embryogenesis systems of most conifer species is very poor.…”
Section: Introductionmentioning
confidence: 99%
“…Factors impacting diverse stages of somatic embryogenesis (embryogenic tissue induction, proliferation culture, pre-treatment, maturation treatment, etc.) and techniques to enhance culture efficiency across various Pine species have been explored [10,[12][13][14][15][16][17][18][19][20]. Furthermore, with the advancement of bioinformatics, researchers are increasingly focusing on the role of genes involved in the various stages of somatic embryogenesis [8,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%